2020
DOI: 10.1038/s41598-020-73989-y
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-26 activates macrophages and facilitates killing of Mycobacterium tuberculosis

Abstract: Tuberculosis-causing Mycobacterium tuberculosis (Mtb) is transmitted via airborne droplets followed by a primary infection of macrophages and dendritic cells. During the activation of host defence mechanisms also neutrophils and T helper 1 (TH1) and TH17 cells are recruited to the site of infection. The TH17 cell-derived interleukin (IL)-17 in turn induces the cathelicidin LL37 which shows direct antimycobacterial effects. Here, we investigated the role of IL-26, a TH1- and TH17-associated cytokine that exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…In a third publication, an activity against biofilm formation of S. aureus was detected which was more pronounced for IL-26 than for the AMP LL-37 (Woetmann et al, 2018). Regarding Mycobacteria (M.) IL-26 has been shown to inhibit growth and reduce viability of M. leprae and M. tuberculosis in axenic cultures as well as within macrophages, probably by inducing lysis by bleb-formation after interaction with lipoarabinomannan (Dang et al, 2019;Hawerkamp et al, 2020). The reason for these functional differences might be due to the different sources and qualities of commercially available IL-26 (Knappe et al, 2000;Hör et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a third publication, an activity against biofilm formation of S. aureus was detected which was more pronounced for IL-26 than for the AMP LL-37 (Woetmann et al, 2018). Regarding Mycobacteria (M.) IL-26 has been shown to inhibit growth and reduce viability of M. leprae and M. tuberculosis in axenic cultures as well as within macrophages, probably by inducing lysis by bleb-formation after interaction with lipoarabinomannan (Dang et al, 2019;Hawerkamp et al, 2020). The reason for these functional differences might be due to the different sources and qualities of commercially available IL-26 (Knappe et al, 2000;Hör et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Unraveling the immunoregulatory effects of IL-26 on macrophages may provide critical insights into the roles of IL-26 in IBD. IL-26 has been reported to polarize macrophages into the M1 phenotype and enhance the expression of CCL20, CXCL8, and CXCL2 mRNA as well as the secretion of TNF-α in THP-1 macrophages ( 23 , 24 ). However, to date, a comprehensive transcriptomic analysis of IL-26-exposed macrophages has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of protein level, IL-26 was higher in noninfected monocytes, which was diminished after infection with tuberculosis. Also, IL-26 levels were somehow higher in non-tuberculous than tuberculous in younger adults but not in elders [62]. According to these results, due to the inhibition of IL-26 production in infected cells, it was assumed that IL-26 exerts significant inhibitory effects on tuberculosis [63].…”
Section: Bacterial Infectionsmentioning
confidence: 95%
“…One inhibitory effect of IL-26 on tuberculosis is attributed to IL-26's unique structure. It has been shown that IL-26 can bind to lipoarabinomannan on the bacterial surface [62]. This capability of IL-26 possibly acts like LL-37 (an antibacterial peptide) and induces pore formation.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation